2023
DOI: 10.3390/vaccines11010114
|View full text |Cite
|
Sign up to set email alerts
|

How Does Digital Media Search for COVID-19 Influence Vaccine Hesitancy? Exploring the Trade-off between Google Trends, Infodemics, Conspiracy Beliefs and Religious Fatalism

Abstract: Digital media has remained problematic during COVID-19 because it has been the source of false and unverified facts. This was particularly evident in the widespread misinformation and confusion regarding the COVID-19 vaccine. Past research suggested infodemics, conspiracy beliefs, and religious fatalism as potential threats to public COVID-19 vaccine hesitancy. However, the literature is primarily void of empirical evidence associating demographic attributes with efforts to build vaccine hesitancy. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…COVID-19 vaccinations were initially administered internationally. However, many nations that promptly immunized a large proportion of their populations found that protective antibodies started to wane over time or were ineffective against COVID-19 variants [ 4 ]. To date, these variants have lingered, often infecting people on a large scale, which has resulted in mounting pressure on health care systems.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 vaccinations were initially administered internationally. However, many nations that promptly immunized a large proportion of their populations found that protective antibodies started to wane over time or were ineffective against COVID-19 variants [ 4 ]. To date, these variants have lingered, often infecting people on a large scale, which has resulted in mounting pressure on health care systems.…”
Section: Introductionmentioning
confidence: 99%
“…Religious fatalism had a negative influence on vaccination against new variants, similar studies indicated that rejection in religious groups is due to the fact that vaccines tend to be an act of interfering with divine providence (12,39). That is, to the extent that conflicting religious beliefs about the origin and consequences of COVID-19 prevail, the less likely vaccine acceptance will be.…”
Section: Discussionmentioning
confidence: 95%
“…The COVID-19 pandemic has often been labeled as a "digital pandemic" due to the widespread dissemination of information facilitated by modern technology. 4,5) These digital tools have facilitated the creation, consumption, and dissemination of false information, thereby making it more challenging for people to differentiate between accurate and false content online. 4,5) Social media platforms have played a pivotal role in disseminating a plethora of information since the beginning of the COVID-19 pandemic.…”
Section: Overview Of the Covid-19 "Infodemic" Pandemicmentioning
confidence: 99%
“…4,5) These digital tools have facilitated the creation, consumption, and dissemination of false information, thereby making it more challenging for people to differentiate between accurate and false content online. 4,5) Social media platforms have played a pivotal role in disseminating a plethora of information since the beginning of the COVID-19 pandemic. As the number of COVID-19 cases increased, searches for COVID-19-related information on social media also witnessed an exponential rise.…”
Section: Overview Of the Covid-19 "Infodemic" Pandemicmentioning
confidence: 99%